Water and energy exchange in East Siberian forest: A synthesis, Agricultural and Forest Meteorology - Maximov, T.; Ohta, T.; Dolman, A.J. (Agricultural and Forest Meteorology, 2008)
This paper summarizes and synthesises the results obtained in several recent studies on water and energy exchange of East Siberian forests located on permafrost. It is found that annual evaporation of these forests shows relatively small inter-annual variation (147-196 mm). The availability of stored water in the permafrost probably functions as a buffering resource that is only used occasionally in very dry years. Surface soil water content shows a 1-year memory to precipitation in Eastern Siberia because the precipitation conditions in previous summers carry over in a frozen condition to the next spring. Modelling shows that evaporation was larger for southern forests than for northern forests. Compared to tundra, taiga forest shows a relatively small Bowen ratio. In an alas system, observations show considerable impact of the distribution of lakes in the vicinity on the observed evaporation fluxes. There appeared to be little difference in the observed Bowen ratio between a young and old larch forest. Surface conductance modelling and upscaling studies note that leaf area index (LAI) was a controlling factor in evaporation. With the permafrost area under strong pressure from climate warming, the need to understand the ecophysiological controls of these forests in East Siberia is paramount. With the data and analysis presented in this special issue becoming available we are now in a better position to model the effects of permafrost degradation on water and energy balances. © 2008 Elsevier B.V. All rights reserved.